BEYOND TRADITIONAL LITERACIES: A MULTIMODAL-BASED INSTRUCTION TO FOSTERING STUDENT DIGITAL LITERACY LEARNING - Kustini, Siti; Suherdi, Didi; Musthafa, Bachrudin (Jurnal Pendidikan Bahasa dan Sastra, 2020)
The fourth Industrial Revolution (IR 4.0) marked by artificial intelligence and cyber-physical systems has transformed the landscape of education including English literacy instruction. Some literacy educators claim that the success of students’ today as millennial kids (Gen-Zs) and future employees has been linked to digital literacy. This term is defined as the skills associated with using digital technology to enable users to locate, organize, understand, evaluate and create information and using those skills to solve problems in technology-rich environments. This study attempts to investigate the extent to which multimodal pedagogy helps improve students’ digital literacy skills in an English for Specific Purposes (ESP) setting in a vocational higher education. A theoretical multimodal semiotic approach along with multiliteracies pedagogy is served as the overarching guideline in the overall instructional procedures grounded specifically from the principles of learner-centeredness, constructivist learning, and social interaction. A qualitative case study approach was adopted to provide an in-depth explication and analysis of students’ literacy development. Data collection included classroom observations and students’ digital artefacts. In the course of the study, the students were engaged in the creation of two digital projects of different genres: digital information report in the form of text-image creation and digital persuasive talk in the form digital video production. The key findings of this study suggest that multimodal pedagogy is an effective instructional method for digital literacy learning in that several aspects of digital literacy had proven to be significantly improved.